Characterization of crop sequences in Argentina spatial distribution and determinants - De Abelleyra, Diego; Banchero, Santiago; Veron, Santiago Ramón (Elsevier, 2025)
CONTEXT: New availability of annual crop type maps in Argentina allows the characterization of crop sequences at field level and the quantification of the occurrence of processes like crop monoculture and rotation. OBJECTIVE: characterization of crop sequences in Argentina and analysis of their spatial distribution patterns in relation to socioeconomic and environmental variables. METHODS: Several crop sequence indices were derived from consecutive crop type maps generated over four growing seasons. Occurrence of different crop sequences was evaluated in relation to spatially explicit information of distance to ports, cadastral unit size (as a measure of farmer’s capitalization), mean annual precipitation, mean annual temperature and soil organic carbon. RESULTS AND CONCLUSIONS: Contrasting to previous reports performed with coarse resolution or point data, most frequent sequences included rotation of soybean, maize and winter cereal crops. Lower cropping intensities were observed both in places with low precipitation and clustered in the agricultural belt in Center Argentina with few environmental limitations. Cases with high frequency of early soybean in the sequence, including cases of four years of monoculture, were also clustered also around the agricultural belt. They were more frequent near to ports and over small cadastral unit size farms. Higher number of cereals in the sequence was observed near ports but preferably over larger cadastral units. Small cadastral units, related to low capitalized farmers, are more averse to tenancy. Shorter distances to ports reduce the fleet cost incrementing the gross margin, being particularly relevant when the additional cost of tenancy is considered. SIGNIFICANCE: This works characterized processes like rotation and monoculture in Argentina at the level where they really occur that is field level, improving the quantification of these processes in relation to previous reports. Results showed limitations to crop intensification related to precipitation availability, and a notable influence of social aspects in the decision of planting and the definition of the crop sequences in areas with no environmental limitations. This information can contribute to the development of public policies in relation to equilibrate the costs for farmers distributed along the county, promoting local agro-industries and developing alternative transportation options to road transport. Incentives to discourage renting the land, especially for small farmers, can promote long term planning with increased crop rotation.